![image](https://tex.z-dn.net/?f=+%5Cfrac%7Bm%5E4-1%7D%7Bm%5E8-1%7D%3C%2Fstrong%3E%3C%2Fem%3E%3C%2Fu%3E+%2C+%3Cu%3E%3Cem%3Em%3D1%2F2%3C%2Fem%3E%3C%2Fu%3E%0A%0A%0A+%5Cfrac%7B%28m%5E4-1%29%7D%7B%28m%5E4-1%29%28m%5E4%2B1%29%7D+%0A%0A%0A+%5Cfrac%7B1%7D%7Bm%5E4%2B1%7D+%0A%0A+%5Cfrac%7B1%7D%7B%281%2F2%29%5E4%2B1%7D+%0A%0A+%5Cfrac%7B1%7D%7B1%2F8%2B1%7D%0A%0A%3D+%3Cu%3E%3Cem%3E%3Cstrong%3E8%2F9+)
,
m=1/2
\frac{(m^4-1)}{(m^4-1)(m^4+1)}
\frac{1}{m^4+1}
\frac{1}{(1/2)^4+1}
\frac{1}{1/8+1}
=
8/9 " alt=" \frac{m^4-1}{m^8-1} ,
m=1/2
\frac{(m^4-1)}{(m^4-1)(m^4+1)}
\frac{1}{m^4+1}
\frac{1}{(1/2)^4+1}
\frac{1}{1/8+1}
=
8/9 " align="absmiddle" class="latex-formula">
(5x^2+x-4)/(x^2+x)=5[(x-0.8)(x+1)]/x(x+1)=5(x-0.8)/x=5x-4/x=
5-4/x
(t^4-bt^2+16)/(t+2)(t^2-4)=[-bt^2-(t^4-16)]/(t^2-4)(t+2)=
-bt^2/(t+2)(t^2-4)-[(t^2-4)(t^2+4)]/(t^2-4)(t+2)=
-bt^2/(t+2)(t^2-4)-[(t-2)
(t+2)(t^2+4)]/(t^2-4)
(t+2)=
-bt^2/(t+2)(t^2-4)-(t-2)=
=
2-t-bt^2/(t+2)(t^2-4)